Association between Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and Components of Metabolic Syndrome in Young Chinese Men - X Ying; Zh Song; Ch Zhao; Y Jiang (Tehran University of Medical Sciences, 2011)
"nBackground: To investigate the prevalence of metabolic syndrome (MetS) in young Chinese population and assess the association between HOMA-IR and different components of MetS in young Chinese men."nMethods: Overall 5576 young Chinese subjects (age range [19-44 yr], 3636 men) were enrolled in, who visited our Health Care Center for a related health checkup from March to December 2008. The international diabetes federation (IDF) definition for MetS was used. The SPSS statistical package, version 11.5 was used for the statistical analysis."nResults: The prevalence of MetS was 21.81% in young men and 5.62% in young women. According to suffering from different numbers of MetS components, the male subjects were divided into four groups. Numbers of MetS components were more and HOMA-IR values were significantly higher. In this male population, the quartile of HOMA-IR was higher, values of triglyceride (TG), fasting plasma glucose (FBG), systolic blood pressure(SBP), diastolic blood pressure(DBP) and waist circumference (WC) were all significantly higher, as well as high density lipoprotein cholesterol (HDL-C) value was significantly lower (P= 0.000). In Spearman's correlation analysis, HOMA-IR was positively correlated with TG, FBG, SBP, DBP and WC, and negatively correlated with HDL-C (r= 0.460, 0.464, 0.362, 0.346, 0.586, -0.357, respectively, all P value= 0.000)."nConclusion: The prevalence of MetS in these young Chinese men was obviously high. Insulin resistance played an important role in occurrence and development of MetS. Waist circumference was the best correlation with HOMA-IR among all components of MetS.